Optimizing per vessel hour capture efficiency for rare, heterogeneously distributed fishes: Invasive grass carp Ctenopharyngodon idella in the Sandusky River - Robert D. Hunter; Song S. Qian; Jason L. Fischer; Ryan Brown; Lucas Nathan; John M. Dettmers; James J. Roberts; Corbin D. Hilling; Matthew R. Acre; Robert Mapes; Ryan Young; Christine M. Mayer (Fisheries Research, 2025)

Improvement of pasture biomass modelling using high-resolution satellite imagery and machine learning - Michael Gbenga Ogungbuyi; Juan Guerschman; Andrew M. Fischer; Richard Azu Crabbe; Iffat Ara; Caroline Mohammed; Peter Scarth; Phil Tickle; Jason Whitehead; Matthew Tom Harrison (Journal of Environmental Management, 2024)

Using multi-platform LiDAR to guide the conservation of the world's largest temperate woodland - Tommaso Jucker; Carl R. Gosper; Georg Wiehl; Paul B. Yeoh; Nat Raisbeck-Brown; Fabian Jörg Fischer; Jason Graham; Helen Langley; William Newchurch; Alison J. O'Donnell; Gerald F.M. Page; Katherine Zdunic; et al. (Remote Sensing of Environment, 2023)

A novel method for extraction and quantification of feather triiodothyronine (T3) and application to ecotoxicology of Purple Martin (Progne subis) - Jonathan M. Branco; Erika Hingst-Zaher; Danielle Dillon; Renee Jordan-Ward; Joe Siegrist; Jason D. Fischer; Luis Schiesari; Frank A. von Hippel; C. Loren Buck (Environmental Pollution, 2023)

Influence of study design and movement behavior on performance of open population spatial Cormack-Jolly-Seber models: application to acoustic telemetry technology - Jason L. Fischer; Travis O. Brenden; Lucas R. Nathan (Environmental Biology of Fishes, 2022)

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Governance in the Face of Extreme Events: Lessons from Evolutionary Processes for Structuring Interventions, and the Need to Go Beyond - Simon A. Levin; John M. Anderies; Neil Adger; Scott Barrett; Elena M. Bennett; Juan Camilo Cardenas; Stephen R. Carpenter; Anne-Sophie Crépin; Paul Ehrlich; Joern Fischer; Carl Folke; Nils Kautsky; et al. (Ecosystems, 2022)

Distribution and migration phenology of Purple Martins (Progne subis) in Brazil - Clarissa O. Santos; Jonathan M. Branco; Maria C. T. D. Belotti; Pedro Abilleira; Joe Siegrist; Jason Fischer; Luciano M. Lima; Mario Cohn-Haft; Erika Hingst-Zaher (Ornithology Research, 2021)

Patterns and mechanisms of invasive plant impacts on North American birds: a systematic review - Scott B. Nelson; Jaime J. Coon; Courtney J. Duchardt; Jason D. Fischer; Samniqueka J. Halsey; Adam J. Kranz; Christine M. Parker; Sarah C. Schneider; Timothy M. Swartz; James R. Miller (Biological Invasions, 2017)

Shifts in microbial food web structure and productivity after additions of naturally occurring dissolved organic matter: Results from large‐scale lacustrine mesocosms - Robert W. Sanders; Sandra L. Cooke; Janet M. Fischer; Samuel B. Fey; Adam W. Heinze; Wade H. Jeffrey; Amy L. Macaluso; Robert E. Moeller; Donald P. Morris; Patrick J. Neale; Mark H. Olson; J. Dean Pakulski; et al. (Limnology and Oceanography, 2015)
Predicting the effects of dissolved organic matter (DOM) on pelagic food webs can be difficult because DOM modifies water column optics and can have contrasting effects on species across trophic levels. We combined large mesocosm, smaller‐scale experiments and autoregressive modeling driven bu DOC concentration or DOM optical quality (colored DOM, or CDOM, measured as DOC‐specific absorbance at 320 nm, SUVA 320 ) to assess how heterotrophic and phototrophic microbial populations were altered in a temperate oligotrophic lake. DOM additions yielded DOC concentrations of 1.6 mg L −1 (control) 2.5 mg L −1 , 3.0 mg L −1 , and 4.3 mg L −1 . Primary (PP) and bacterial (BP) production as well as heterotrophic and autotrophic protist abundances were stimulated in the higher DOM additions. BP responded rapidly to DOM additions, but unlike PP, returned to the level of controls within 2–7 d. A bioassay showed that the DOM was a nitrogen source for phytoplankton. The two models revealed that BP and edible phytoplankton were stimulated by CDOM (SUVA 320 ), but only BP was stimulated by DOC concentration. Ultraviolet radiation (UV) inhibited protists in both models, but stimulated edible phytoplankton only in the SUVA 320 model runs. These results suggest that in transparent oligotrophic lakes large influxes of terrestrial (high SUVA 320 ) DOM will stimulate the microbial food web by providing a nutrient subsidy to bacteria and reducing exposure of protists to damaging UV. Nutrients associated with moderate DOM input may also stimulate PP relative to BP, as was observed in these and other experiments, rather than causing an overall system shift toward heterotrophy.

Evidence of the St. Clair-Detroit River System as a dispersal corridor and nursery habitat for transient larval burbot - Darrin E. McCullough; Edward F. Roseman; Kevin M. Keeler; Robin L. DeBruyne; Jeremy J. Pritt; Patricia A. Thompson; Stacey Ireland; Jason E. Ross; Dustin Bowser; Robert D. Hunter; Dana Castle; Jason L. Fischer; et al. (Hydrobiologia, 2015)

Categorizing wildlife responses to urbanization and conservation implications of terminology - Jason D. Fischer; Sarah C. Schneider; Adam A. Ahlers; James R. Miller (Conservation Biology, 2015)

Two-sided edge responses of avian communities in an urban landscape - Sarah C. Schneider; Jason D. Fischer; James R. Miller (Urban Ecosystems, 2015)

Effects of experience and a visual aid on ptilochronology - Laura M. Frasz; Jason D. Fischer; James R. Miller (Journal of Ornithology, 2014)

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.